2017
DOI: 10.1097/md.0000000000006523
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic skin response and heart rate variability in predicting autonomic disorders in patients with Parkinson disease

Abstract: The purpose of this study was to evaluate sympathetic skin response (SSR) and heart rate variability (HRV) in determining autonomic nervous system (ANS) involvement in patients with Parkinson disease (PD). Forty-eight idiopathic PD patients and 30 healthy controls participated in this study. SSR, HRV, Unified Parkinson's Disease Rating Scale (UPDRS) III, the Scales for outcomes in Parkinson's Disease-Autonomic (SCOPA-AUT), Hoehn and Yahr (H&Y) scale were evaluated. Absent lower limb SSR was determined unilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…As a note, age is a rather important factor affecting SSR. Two previous studies with 48 and 58 PD patients, respectively, showed inverse correlations of SSR amplitude with SCOPA-AUT and UPDRS tremor scores (14,33). On the other hand, Giza et al (15) studied 29 PD patients without clinical manifestation of dysautonomia and found that their SSR was similar to controls regardless a presence of correlation between UPDRS-III score and SSR.…”
Section: Discussionmentioning
confidence: 88%
“…As a note, age is a rather important factor affecting SSR. Two previous studies with 48 and 58 PD patients, respectively, showed inverse correlations of SSR amplitude with SCOPA-AUT and UPDRS tremor scores (14,33). On the other hand, Giza et al (15) studied 29 PD patients without clinical manifestation of dysautonomia and found that their SSR was similar to controls regardless a presence of correlation between UPDRS-III score and SSR.…”
Section: Discussionmentioning
confidence: 88%
“…Taken together, the HRV measurements suggest that propolis has a cardioprotective effect on the 6-OHDA rat model of PD. Previous studies have shown statistically significant reductions in frequency domain and time domain measures (RMSSD and SDNN) of HRV, suggesting compromised autonomic cardiovascular regulation in PD patients, which is associated with greater risk of mortality [ 95 , 96 , 97 , 98 ]. Studies have suggested that HRV analysis is a major approach for assessing early sign of autonomic dysfunction in patients with PD and is more accurate than the conventional cardiovascular tests that are commonly used, such as Valsalva maneuver and head-up tilt test, among others [ 22 , 24 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…PD is known to decrease patient’s heart rate variability (HRV) 28,29 . Several studies on cardiologic conditions reports an association between reduced HRV with sudden unexpected death 30 .…”
Section: Discussionmentioning
confidence: 99%